Visual Communication Media Design To Increase Awareness Towards Anime Lovers Identity - Victoria Soetanto; Cindy Muljosumarto; Merry Sylvia (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2025)
Weeaboo is one form of evidence of the popularity of Japanese subculture, referring to fans who are obsessed with Japanese culture in a negative context. Weeaboos are often stereotyped as fanatical, perverted, smelly (like garlic), and antisocial. As a result of this stigmatization, fans have begun to classify themselves with the term "anime lovers" as a way to differentiate from weeaboos. However, this term is not widely known by the general public. Therefore, awareness efforts are needed to increase public knowledge about the identity of anime lovers through visual communication media . Visual communication media serves as a representation of the voice of anime lovers who do not want to be associated with negative stereotypes. The research will use a descriptive qualitative method to analyze the perspectives of specific groups. The stages include conducting interviews with anime lovers, Japanese culture experts, and the general public to gain understanding from both sides. The results of the data analysis will produce insights that form the foundation of the message content (what to say) and the big idea that shapes the entire campaign content.